UJI INFEKSI Phaeophleospora spp. PADA KLON HIBRID Eucalyptus grandis x Eucalyptus urophylla - Paulus Stefan S. N; Nelly Anna; Edy Batara Mulya Siregar (Program studi Kehutanan USU, 2015)
Eucalyptus is a species that widely used in pulping industry. Phaeophleospora is one of the pathogens that attack the leaves of young Eucalyptus plant. The purposes of this research were to characterize the leaf disease symptoms and to measure disease severity and disease incidence caused by Phaeophleospora spp. on two-month-old IND 47, IND 61, dan IND 66 Eucalyptus grandis x Eucalyptus urophylla hybrid clones. Inoculation was implemented with spray method. The leaves symptoms caused by Phaeophleospora showed the same symptoms on clones IND 47, IND 61, and IND 66. The early symptoms were the yellow dots on the upperside of the leaves and then developed into spots. The advanced symptoms were reddish spots on the upperside of the leaves and black spores on the underside of the leaves. Three clones were classified as resistant in disease severity measurement, meanwhile in disease incidence measurement, three clones were classified as moderately resistant. Keywords : Phaeophleospora, infection test, symptoms, resistant